PENERUSAN BUDAYA KELUARGA DALAM PEMBENTUKAN KONSELING DIGITAL DI BIDANG PENDIDIKAN DAN PSIKOLOGI - Fika Dwii Mulia; Neviyarni Neviyarni (Universitas Negeri Medan, 2026)
The development of technology-based counseling services has become an important part of modern educational and psychological practices, especially for reaching individuals and families who face limitations in accessing conventional services. However, the adoption and sustainability of digital counseling does not take place in a socially neutral space. This study aims to synthesize empirical evidence regarding the role of family cultural transmission in shaping the meaning, acceptance, and use of technology-based counseling services. The study uses a Systematic Literature Review (SLR) approach with reference to the PRISMA 2020 guidelines. The search was conducted on the Scopus database for articles published between 2020 and 2026 and focused on the contexts of education and psychology. The selection process resulted in four main studies that were analyzed through narrative synthesis. The results of the study show that families act as agents of transmission of values, norms, and relationship patterns that significantly influence individuals' attitudes toward digital counseling. Family cultural values also shape trust in services, decision-making patterns, and the sustainability of technology-based counseling use. These findings emphasize the importance of integrating sociological and anthropological perspectives in the development and implementation of digital counseling to make it more contextual, inclusive, and relevant to educational and psychological practices in various cultural settings.